Immaginare l'altrove nell'epoca dell'Antropocene Media, confini e cambiamenti climatici - CAPPI, VALENTINA (Consumo, Comunicazione, Innovazione, 2023)
This book explores the processes through which particular places take shape in the imaginaries, perceptions and narratives of people who do not inhabit them, or who have inhabited them only recently. The ways in which we imagine the elsewhere are the product of stories collectively constructed and reproduced by a multiplicity of actors and through a variety of communicative tools and practices. These narratives shape our perceptions of others, the way we relate to them, and the politics that regulate cohabitation on Earth. In this book, the elsewhere becomes a device for exploring some of the ways in which human beings interact with each other, establish distinctions and alliances, trace borders, and enact change in the epoch of the Anthropocene. Through four phenomenologies of the elsewhere (Europe, Africa, the transnational space, climate change), the author reflects on the opportunity to decentralize one's own gaze, in time and space, in order to imagine other ways of worldmaking.